Investigating the effect of translated international logos on brand awareness and corporate image within the Arabian Gulf regions - Mohamed, Khaled M.; Daher, Manar; Gad, Salah; Zakarneh, Bilal (Frontiers in Communication, 2025)
IntroductionThis study examines the impact of translating international logos into Arabic on brand awareness and corporate image within the Arabian Gulf region. The research draws on semiotic theory, brand culture frameworks, localization strategies, and cognitive processing models to understand how culturally adapted visual identities influence consumer perceptions.MethodsA quantitative, cross-sectional survey was conducted with 217 participants across Gulf Cooperation Council (GCC) countries. The study measured emotional engagement, cultural relevance, brand recognition, and perceptions of professionalism. Descriptive and inferential statistical analyses, including correlation and regression tests, were applied to assess the relationships between logo translation and key brand outcomes.ResultsThe findings revealed that translating logos into Arabic significantly enhances brand recognition, with 63.5% of respondents reporting improved recall. In addition, 78.3% associated visually harmonious translated logos with higher professionalism and corporate commitment. Translated logos were also perceived as more culturally relevant and emotionally engaging, fostering stronger trust and connection between brands and consumers.DiscussionThe results highlight the strategic value of culturally adapted visual identities in enhancing brand salience and corporate reputation in the Gulf region. By balancing global brand consistency with local cultural integration, marketers and brand managers can strengthen consumer trust and engagement. The study contributes to cross-cultural branding literature and offers practical implications for global companies operating in competitive GCC markets.